Candidate screening of the TRPC3 gene in cerebellar ataxia. - Becker, E; Fogel, B; Rajakulendran, S; Dulneva, A; Hanna, MG; Perlman, S; Geschwind, D; Davies, K (2011)
The hereditary cerebellar ataxias are a diverse group of neurodegenerative disorders primarily characterised by loss of balance and coordination due to dysfunction of the cerebellum and its associated pathways. Although many genetic mutations causing inherited cerebellar ataxia have been identified, a significant percentage of patients remain whose cause is unknown. The transient receptor potential (TRP) family member TRPC3 is a non-selective cation channel linked to key signalling pathways that are affected in cerebellar ataxia. Furthermore, genetic mouse models of TRPC3 dysfunction display cerebellar ataxia, making the TRPC3 gene an excellent candidate for screening ataxic patients with unknown genetic aetiology. Here, we report a genetic screen for TRPC3 mutations in a cohort of 98 patients with genetically undefined late-onset cerebellar ataxia and further ten patients with undefined episodic ataxia. We identified a number of variants but no causative mutations in TRPC3. Our findings suggest that mutations in TRPC3 do not significantly contribute to the cause of late-onset and episodic human cerebellar ataxias.